Readiness for hospital discharge on people after hip replacement surgery in Vietnam: A cross-sectional study - Huu Phuoc Nguyen; Ba Hai Mai (Tehran University of Medical Sciences, 2024)
Background & Aim: Readiness for hospital discharge is closely linked to post-operative complications, readmission rates, and the post-discharge health status of patients after hip replacement surgery. This study aimed to assess discharge readiness and identify the factors that predict it in patients undergoing hip replacement surgery. Methods & Materials: This cross-sectional descriptive study included 112 patients who had undergone hip replacement surgery at Hospital X in Middle Vietnam. Participants were selected using a convenience sampling method, and data were collected within 4 hours before hospital discharge. The Readiness for Discharge Scale, developed by Weiss et al. was used to measure discharge readiness. Data analysis was conducted using SPSS 20.0 statistical software. Results: The average discharge readiness score was 6.06± 2.10, indicating a low discharge readiness level. Multivariable linear regression analysis revealed that age, living conditions, planned admission, previous admission for the same diagnosis, and length of hospital stay significantly predicted 78.5% of the variance in discharge readiness (F= 77.626, p< 0.001). Among these factors, the strongest predictor was previous admission for the same diagnosis (β= 0.341, p< 0.001), followed by planned admission (β= 0.324, p< 0.001). Conclusion: The findings indicate that patients' readiness for discharge after hip replacement surgery remains low, with various factors influencing their readiness. Nurses caring for these patients should consider these factors to improve discharge readiness and patient outcomes.